2018
DOI: 10.3389/fphar.2018.00667
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Metabolomics With Pharmacodynamics to Elucidate the Anti-myocardial Ischemia Effects of Combination of Notoginseng Total Saponins and Safflower Total Flavonoids

Abstract: Notoginseng (Sanqi), the roots and rhizomes of Panax notoginseng and safflower, the flowers of Carthamus tinctorius, are widely used traditional Chinese medicines (TCMs) for the treatment of cardiovascular diseases. Positive evidences have fueled growing acceptance for cardioprotective effects of the combination of the notoginseng total saponins and safflower total flavonoids (CNS) against myocardial ischemia (MI). However, the underlying cardioprotective mechanisms of CNS are still obscured. Metabolomics is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 70 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…20110301) was deposited at Modern Research Center for Traditional Chinese Medicine, Peking University (Beijing, China). SF was prepared following the protocol reported by Meng, in which the content of HSYA was 10.53% [10]. The ratio of NS and SF was 6:5 in CNS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20110301) was deposited at Modern Research Center for Traditional Chinese Medicine, Peking University (Beijing, China). SF was prepared following the protocol reported by Meng, in which the content of HSYA was 10.53% [10]. The ratio of NS and SF was 6:5 in CNS.…”
Section: Methodsmentioning
confidence: 99%
“…Notoginseng Radix et Rhizoma (notoginseng) in combination with Carthami Flos (safflower), has been commonly used for the prevention and treatment of cardiovascular diseases [9,10]. Notoginseng is an important Chinese medicinal herb utilized for the treatment of pectoris and coronary artery disease [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial ischemia-induced infarction is one of the leading causes of human death worldwide. The benefits of either Carthamus tinctorius extract (CTE) or notoginseng total saponins (NGTS) towards myocardial ischemia injury on rats have been well defined, and more interestingly, previous studies have demonstrated that better cardio-protective effects were observed when using their combination preparation (CNP) [1][2][3]. However, the underlying synergetic mechanisms of CTE and NGTS combination, their pharmacokinetic (PK) interactions in particular, still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous pharmacological evaluations optimized a relatively low dosage CNP for the anti-myocardial ischemia effect [2]. Furthermore, the cocktail method usually suffers from extensive CYP450 crossover within the probe substrates [7].…”
Section: Introductionmentioning
confidence: 99%